Performance Analysis of Plate Punching and Bending Machine Combination - Fazri Zaini Ibrahim; Yohanes Yohanes (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2021)
The plate punching and bending combination machine is a machine that belongs to the press type with the use of a punch and a die to make holes or bends in a plate work-piece. This machine uses a hydraulic drive with a maximum working pressure of 700 Bars, which is used as a punch force to work-piece. But, it is not known the value of working pressure this frame can withstand. Therefore, machine performance becomes unknown such as punch force that can be used, work-piece thickness, whole circumference and type of material that can be machined. In this paper, the analysis is carried out using simulation and experimental methods. The simulation method is carried out using Autodesk Inventor software to determine the critical location, which is then measured by experiment. The experimental method is carried out by measuring the stress and deflection. Voltage measurement on the frame is carried out using a strain gauge sensor and measurements are carried out using a dial indicator. The application of a safety factor is 1.5 based on the yield strength of ASTM A36 as the frame material. The deflection that has occurred is 1.15 mm, the maximum working pressure obtained is 27.7 Bars. The maximum punch force is 5441 N.